Specification of norms of a protein feed of dairy cows in the first phase of a lactation - EUGENY LEONIDOVICH KHARITONOV, (International Journal of Pharma and Bio Sciences, 2017)
Two experiments on cows were completed to specification of norms of a protein feed for cows in the beginning of a lactation on first -heifers a method of the periods (4Ñ…3) and a method of the groups - periods (3Ñ…2) on pubertal cows of black-and-white breed in conditions of a vivarium in the first 2 months of a lactation. In all periods of experiment of a cow received hay - silage-concentrates rations. In the first experience, increasing a level of a metabolic protein in a ration on 5,8 and 11,7 %. In the second experience the trial group obtained in structure a ration of a metabolic protein on 16 % and on 9,5 % is more than control group due to different structure of a mixed food. The researches lead by us have shown, that for rising milk yields at cows with a normal fatness before calving and medium a level of milk efficiency on a pique of a lactation up to 30Ðºg milk, production of milk protein in the first phase of a lactation of cows (up to 10 %) is possible for increasing by augmentation of a level of metabolic protein in rations on 10 % till 45-th day of a lactation. Further of cows it is necessary to nurture on existing norms of a metabolizable protein.